ANALISIS MANAJEMEN KETENAGAAN KESEHATAN TERHADAP PENCAPAIAN INDIKATOR KINERJA PUSKESMAS PADA UPTD PUSKESMAS TANAH PASIR KABUPATEN ACEH UTARA TAHUN 2021 - elfida fitri (Jurnal Inovasi Kesehatan Masyarakat, 2022)
To provide maximum and excellent public services to the community, the success of the puskesmas in carrying out its program is determined by the availability of human resources (HR) that are balanced between medical personnel on the one hand and promotive and preventive personnel on the other. The type of research used is qualitative research to analyze Health Manpower Management on the Achievement of Health Center Performance Indicators at UPTD Puskesmas Tanah Pasir, North Aceh Regency based on applicable standards. The research period starts from December 2021 to Mei 2022. The research informants consist of 4 people, namely the Head of the UPTD of the Tanah Pasir Health Center, the Head of the TU UPTD of the Tanah Pasir Health Center, the Head of the Health Resources Division and the Head of the Sub-Division of Personnel. The Health Manpower Management at the UPTD Tanah Pasir Public Health Center has used the Minimum Manpower Standards based on the Minister of Health Regulation no. 43 of 2019 in determining the number and types of health personnel, only in the fulfillment of health workers in all programs there is still a shortage of nutrition and public health personnel (slinging staff). There were quite a number of MSS Performance Indicators during the pandemic that were not achieved, constrained by the distribution of health workers in various additional programs related to pandemic response so that several programs experienced a decline in services as a direct result of the concentration of activities on the pandemic response program. The management of the Puskesmas is expected to be able to make proposals regarding the shortage of nutrition and public health workers (health workers). It is necessary to carry out regular monitoring and evaluation related to the fulfillment of health workers according to the number and type of health workers based on the needs of each health service program, not only based on the minimum standard of personnel at the Puskesmas.